Prevalência de alterações cromossômicas constitucionais e relacionadas a neoplasias de medula óssea em 13 anos de análise citogenética no estado do Ceará - Pinheiro, Gilcivania Ferreira Alves (2024)
Cytogenetics is the field of genetics that studies the chromosome, among others, through karyotype analysis. Were analyzed karyotypes of 2,242 patients, 1757 cases related to suspected bone marrow neoplasia and 485 related to suspected constitutional changes. Cases related to bone marrow neoplasia were analyzed from january 2010 to june 2022 and constitutional cases (peripheral blood, amniotic fluid, umbilical cord blood and placenta), from december 2016 to June 2022. The main clinical indications for performing bone marrow karyotype exams were myelodysplastic syndrome with 954 exams (54,29%), acute leukemias with 246 exams (14%), chronic leukemias with 206 (11,72%), leukopenia with 112 exams (6,37%) and bone marrow transplantation with 104 exams (5,91%), these cases are mostly related to women over 60 years of age, even with myelodysplastic syndrome. Bone marrow cytogenetic analysis identified cytogenetic changes in almost a quarter (24,75%) of cases, such as: t(9;22) (17,33%), del(5q) (13,33%) and cases with complex karyotype (9,42%). In relation to constitutional cases, there were 412 (84,95%) cases with analysis postnatal period using peripheral blood and 73 cases (15,05%) in the prenatal period, from 51 cordocentesis (10,51%), 17 amniotic fluid samples (3,5%) and 5 placenta samples (1,03%). The cordocentesis, amniotic fluid and placenta analyzes were the first carried out in the state of Ceara, all coming from the Assis Chateaubriand Maternity School. Analysis of this period had a normal karyotype in 30% of cases and 41% showed chromosomal changes. The chromosomal changes that were most common in the prenatal period were sexual differentiation disorders (33,33%) with 46,XY karyotype in female pregnancy, followed by trisomy 18 (30%) and trisomy 21 (13,33%). In relation to postnatal analyses, 36,40% of the cases referred were able to confirm suspected diagnoses that were not even considered in the clinical indication. Another 58% of cases were normal and 94,4% of these analyzes from peripheral blood were conclusive. The most common findings were trisomy 21 (43,33%), followed by sexual differentiation disorders (14%) and trisomy 18 (11,33%). Through these data, an important cytogenetic portrait of the local health reality can be observed, with the most frequent changes in recent years. If these exams were carried out in outsourced services, the costs would have a huge financial impact, with amounts reaching around 3.5 million reais, just for the karyotype analysis.